Response of Waste Foundry Sand Backfilled Retaining Wall - Kumar, Ankit (My University, 2024)
The rapid growth of cities has created a rising demand for natural resources, mainly sand, in various construction activities. This escalating demand has resulted in environmentally harmful practices like sand mining from river beds, threatening the ecology. Consequently, there is an urgent call to replace natural sand in construction. It is essential to promote alternative materials that maintain engineering performance to address this issue. Recent decades have shifted towards green industrialization, emphasizing sustainable construction practices to mitigate environmental impacts. The design of retaining walls is vital for infrastructure projects, preventing soil erosion, stabilizing slopes, and supporting grade changes. Choosing suitable backfill materials for these walls is essential for ensuring structural integrity and long-term stability. While traditional backfill materials like natural sands have been widely used, the growing emphasis on sustainable practices and minimizing environmental impact has sparked interest in exploring alternative construction materials, aligning with the United Nations Sustainable Development Goal 11. The present study aims to assess the overall viability of replacement of natural sand with waste foundry sand (WFS) in the backfill of retaining walls. The WFS from four different metal casting foundries (aluminium, gunmetal, iron and cast iron) is considered. Physical, chemical, geotechnical, microsturctural, thermal, pH and leaching properties of these WFS samples are quantified to check the suitability of WFS for backfill of retaining wall. The results of these tests show that WFS from cast iron foundry (CI-WFS) is most suitable for use as geomaterial. So, CI-WFS is used to study the response of model retaining wall backfilled with sand-WFS mixtures.The model retaining wall study includes the assessment of lateral earth pressure and displacement of the model wall with active and at-rest boundary conditions. This parametric study quantifies the effect of WFS fraction, geogrid layers, backfill density and surcharge loading on the response of the retaining wall.The natural sand is replaced with WFS at 20% replacement level by weight. The values of angle of friction measured from CD-DST tests are considered to optimize the replacement level. The angle of friction is found to be maximum for 40% replacement level. The interaction properties of these mixtures with geogrid and model wall material are measured with large box direct shear tests at different relative densities. In total, 28 distinct laboratory-scale physical model experiments have been performed on a 0.5 m high retaining wall. The earth pressures and wall displacements are measured at relative depths of z/H = 0.2, 0.5, 0.7 and z/H = 0.1, 0.3, 0.5, 0.7 respectively. The gradually increasing surcharge load is applied gradually on an iron plate placed at the surface of the backfill. The results of interaction properties are consistent with model tests. The earth pressure reduces by 10% and 22% at a relative depth of z/H = 0.2 and 0.5, respectively, with 40% replacement. Furthermore, the maximum lateral displacement in the active case reduces by 35% compared to control case of 100% sand. In the “at-rest” state, introducing a single layer of geogrid reduces the earth pressure by 30%. This reduction amplifies to 50% when an additional layer of geogrid is included. The lateral displacement of the wall decreases by 30% and 50% when one geogrid and two geogrid layers are included, respectively, in the active case. The earth pressure results from numerical and available theoretical approaches are compared with the experimental results. 2-D simulations based on finite element methodology are modelled in ABAQUS software with CAE package. The part, material, constraint, loading, interaction, element and meshing properties are defined to simulate most experimental conditions. Numerical analysis results of plane strain soil elements modelled with Mohr Coloumb properties are compared reasonably well with the experimental results. An important aspect of future research is a comprehensive assessment of the environmental impact of using foundry sands in geotechnical applications. In the present study, environmental impact of WFS backfilled retaining wall is quantified by Life Cycle Assessment (LCA) approach. Construction of retaining wall with natural sand, WFS and 40% WFS-sand mixture are considered as functional units. The 15-midpoint and 2-endpoint impact indicators are reported using openLCA software and Ecoinvent 3.8 database. 100% WFS and 40% sand-WFS mixture backfill reduces renewable energy demand by 89.14% and 37.58%, respectively, compared to a 100% natural sand backfill.
Keywords: retaining wall; backfill; waste foundry sand; geotechnical, sustainable material